Design and Development of Biometric Enabled Advanced Voting System (International Journal of Innovative Research in Computer Science & Technology, 2020)
The focus of this paper is to design and  development of a biometric enabled biometric electronic  voting machine. The proposed biometric electoral voting  system allows the user to scan fingerprint and iris so that his  or her credentials can be compared to existing fingerprint  and iris images already stored in the system's database.  Counting is going on right away, making the voting process  more efficient, faster and safer. This system requires the  identification of the voter Aadhaar card, the voter's thumb  impression as well as the iris image. Voter's complete data,  including all voters' fingerprint and iris image, is collected  and stored in the database. While voting, the voter gives  their Aadhaar card details and puts eye in front of the iris  camera and finger inside a fingerprint scanner, the system  looks for the seal already provided in the data base, and then  compares the iris image to authenticate the voter's identity.  If the data matches, the system commands the voter to vote  through the electronic voting machine. If the fingerprints  do not match, the voting presiding officer looks for the  registration, or the iris image does not match after the  fingerprint match, the voter is not allowed to vote, consider  it vote rigging.
Keywords: Electronic voting machine; iris; fingerprint